2008
DOI: 10.1116/1.3039681
|View full text |Cite
|
Sign up to set email alerts
|

Second-order resonant ZnO-based film bulk acoustic resonator devices and thermal techniques to improve their resonant characteristics

Abstract: Articles you may be interested inViscosity sensor using ZnO and AlN thin film bulk acoustic resonators with tilted polar c-axis orientations J. Appl. Phys. 110, 094511 (2011); 10.1063/1.3657781Mass sensitivity of thin film bulk acoustic resonator sensors based on polar c-axis tilted zinc oxide and aluminum nitride thin film Field and temperature dependent parameters of the dc field induced resonances in Ba x Sr 1 − x Ti O 3 -based tunable thin film bulk acoustic resonatorsIn this article, the authors describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The breadth of nanostructures formed by ZnO is breathtaking, and includes rods [6], needles [7,8], plates [9], flowers [10], belts [1], and helices [11]. Examples of reported nanodevices include field emission transistors [12,13], ultrasensitive gas sensors [14], cantilevers [15], resonators [16,17], transducers [18], actuators [19], LEDs [20], and lasers [21]. Studies have found the properties of ZnO crystals to be intricately related to their size and shape [22].…”
Section: Introductionmentioning
confidence: 99%
“…The breadth of nanostructures formed by ZnO is breathtaking, and includes rods [6], needles [7,8], plates [9], flowers [10], belts [1], and helices [11]. Examples of reported nanodevices include field emission transistors [12,13], ultrasensitive gas sensors [14], cantilevers [15], resonators [16,17], transducers [18], actuators [19], LEDs [20], and lasers [21]. Studies have found the properties of ZnO crystals to be intricately related to their size and shape [22].…”
Section: Introductionmentioning
confidence: 99%
“…The breadth of nanostructures formed by ZnO is breathtaking, and includes rods [6], needles [7,8], plates [9], flowers [10], belts [1], and helices [11]. Examples of reported nanodevices include field emission transistors [12,13], ultrasensitive gas sensors [14], cantilevers [15], resonators [16,17], transducers [18], actuators [19], LEDs [20], and lasers [21]. Studies have found the properties of ZnO crystals to be intricately related to their size and shape [22].…”
Section: Introductionmentioning
confidence: 99%